Formation of chiral CO polyhedral crystals on icy interstellar grains. Issue 1 (27th April 2021) - Kouchi, Akira; Tsuge, Masashi; Hama, Tetsuya; Niinomi, Hiromasa; Nakatani, Naoki; Shimonishi, Takashi; Oba, Yasuhiro; Kimura, Yuki; Sirono, Sin-iti; Okuzumi, Satoshi; Momose, Munetake; Furuya, Kenji; et al.
ABSTRACT: The crystallinity and morphology of solid carbon monoxide (CO) on icy interstellar grains were examined by observing the deposition, crystallization, and UV and electrons irradiation of solid CO using transmission electron microscopy. Herein, we found that solid CO deposited in molecular clouds was crystalline, and that even if amorphous CO was deposited, amorphous CO crystallized within 10 3 yr at 10 K. Conversely, crystalline CO was not amorphized by UV rays or electron beam at 10 K. These results indicated the occurrence of chiral crystalline CO instead of amorphous CO in space. Furthermore, the large surface diffusion coefficients of CO on eamorphous H2 O and crystalline CO at 10 K facilitated the morphological equilibration of crystalline CO. Bad wetting of crystalline CO with amorphous H2 O proved that the morphology of the ice grains was not spherical with an onion-like structure, as hitherto assumed, but rather it was a polyhedral crystalline CO attached to amorphous H2 O. This has important implications for phenomena associated with the collision and subsequent sticking between ice grains, surface chemical reactions, non-thermal desorption of molecules and the origin of homochirality in interstellar biomolecules.